Evaluation of alveolar bone changes of jaws in periodontitis patients with and without dental fluorosis using cone-beam computed tomography - Kharidhi Laxman Vandana; Mohanan Thushara; S. Shivaprasad (SRM Journal of Research in Dental Sciences)
Background: The periodontal management in patients affected by dental fluorosis and its effect on jawbone quality presents a blind spot due to a lack of knowledge. Aim: The aim of the study was to determine how dental fluorosis affects the periodontium in terms of cortical plate thickness, trabecular pattern, and bone density (BD), and the study compares patients with and without dental fluorosis who have periodontitis. Materials and Methods: There were a total of 30 patients in each of both groups, nonfluorosed periodontitis and fluorosed periodontitis. The age group of 35–50 years belonged to both sexes. The clinical and radiographic characteristics (BD, trabecular pattern, and cortical plate thickness) of each group were assessed and evaluated. Results: Thicker buccal cortical plate was found in the fluorosed healthy group (1.1 mm). The BD of the fluorosed diseased group was found to be greater than that of the nonfluorosed diseased group. Significant differences between several trabecular patterns were visible in the trabecular pattern (P = 0.02). Nevertheless, both healthy (63%) and diseased (80%) fluorosed sites exhibited the most significant levels of thick dense pattern. Conclusion: The fluorosed and nonfluorosed groups had significantly different bone quality, according to cone-beam computed tomography (CBCT) results.